Analysis Of English Use on Social Media in Generation Z Students Study on Students of Vocational High School (Rural Area) - Aldin Ramdani; Lutfiana; Novala Arum Salsabillah; Estiningtyas Sholikhah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Generation Z is a digital native generation that has grown up along with the development of information and communication technology, especially social media, which has significant implications for the shift in the English learning paradigm from formal to informal. This study aims to examine the pattern of the use of social media as an alternative learning space for Generation Z students in rural areas. Despite the growing body of research on social media-assisted language learning, most studies have focused on urban students or university contexts, leaving limited evidence from rural vocational schools where access to authentic English-speaking environments remains restricted. Therefore, students of Vocational High School were selected because they represent Generation Z learners in rural areas who rely heavily on digital platforms to access English-language input. This study uses a quantitative descriptive approach with a cross-sectional survey design to map the perception, intensity of use, and form of student involvement in English learning activities mediated by social media algorithms. Algorithm-mediated learning refers to language exposure that occurs through personalized content recommendations generated by social media algorithms such as TikTok's For You Page (FYP) and Instagram Reels. Data were collected from 22 students through a closed-ended questionnaire based on the Likert scale and observation of digital activities.  The findings revealed high levels of exposure to English-language content (M = 4.36; 87.2%) and strong interest in learning English through social media (M = 4.57; 91.4%).The results show that social media is used as a means of self-taught learning and project-based learning mediated by algorithms such as platforms such as TikTok and Instagram.